Effects of a Safety Letter on Metoclopramide Use in Korea: An Interrupted Time-Series Analysis - Kim H; Suh HS (Dove Medical Press, 2020)
Hyungtae Kim, Hae Sun Suh College of Pharmacy, Pusan National University, Busan, South KoreaCorrespondence: Hae Sun SuhCollege of Pharmacy, Pusan National University, Busandaehak-Ro 63 Beon-Gil-2, Geumjeong-gu, Busan 46241, South KoreaTel +82-51-510-2528Fax +82-51-513-6754Email haesun.suh@pusan.ac.krBackground: The Korean Ministry of Food and Drug Safety (MFDS) issued a safety letter regarding metoclopramide use and its adverse drug event of extrapyramidal disorder in October 2013. However, this safety letter had controversial effects on pharmacovigilance and management policies. The objective of this study was to estimate the impact of this government safety letter on the use of metoclopramide.Patients and Methods: We conducted an interrupted time-series analysis using national claims data from January 2011 to December 2015 to assess the difference in metoclopramide utilization (ie, the total number of prescriptions per month, the average administration period per prescription per month, and the average dose per prescription per month) before and after the publication of the safety letter in October 2013.Results: The number of prescriptions, the average administration period per prescription, and the average dose per prescription of metoclopramide decreased after the publication of the safety letter. Notably, the decrease in the average administration period per prescription after the safety letter was statistically significant.Conclusion: Our results indicate that the changes in the number of prescriptions, dose, and the duration of prescription may have occurred as a result of the restrictions and recommendations in the safety letter. Further research is needed to optimize the use of metoclopramide and to identify the risk of adverse drug events since the safety letter was issued.Keywords: metoclopramide, extrapyramidal disorders, safety alert, ministry of food and drug safety